Polymer expanded microsphere doped modified fluororubber foam composite material and application thereof
By doping polymer expansion microspheres and nano-silicon dioxide balls in fluoroelastic rubber and adopting vulcanization process, the problem of insufficient performance of fluoroelastic foam composite materials in high temperature and strong corrosion environments is solved, and the mechanical properties of the material are improved and reduce conductivity, suitable for a variety of high-end applications.
Patent Information
- Application Number
- CN202411502010.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-07
AI Technical Summary
The existing fluoroelastic foam composite materials lack sufficient performance in high temperature and strong corrosion environments, and have low mechanical strength, modulus and hardness, which limits their application in aerospace, automobiles and other fields.
Modified fluoroelastic foam composite materials are prepared by doping polymer expansion microspheres and nanosilicon dioxide spheres in fluoroelastic rubber and using vulcanization process to optimize foaming conditions and filler content to improve the mechanical and thermal insulation properties of the material.
The mechanical properties of fluoroelastic foam composites have been improved, especially in terms of tensile strength and hardness, and the conductivity has been reduced, and it is suitable for electrical insulation and semiconductor sealing fields.
Smart Images

Figure CN119391109A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fluororubber, and in particular to a polymer expanded microsphere doped modified fluororubber foam composite material and application thereof. Background Art
[0002] Foaming materials are gradually used in various industries due to their advantages such as low density, good cushioning performance and excellent thermal insulation performance. At present, most polymer materials can be used as the matrix to prepare foaming materials, such as rubber, plastic, elastomer, etc. However, these foaming materials generally have poor solvent resistance and heat resistance, which limits their scope of use. Fluororubber (FKM) is a synthetic elastomer with fluorine atoms on the main chain or side chain. Due to the presence of fluorine atoms, FKM has excellent oil resistance, corrosion resistance, aging resistance and heat resistance and is widely used in the automotive industry, aerospace, sealing materials and other fields, thus becoming an ideal foaming material.
[0003] At present, heat-insulating and corrosion-resistant fluororubber foam composite materials are relatively rare in the market. They have great application potential and broader development prospects in harsh fields such as high temperature and strong corrosion, such as chemical industry, aerospace, automobile, and electronics. The foaming methods of FKM mainly include physical foaming and chemical foaming. Among them, physical foaming is widely used due to its advantages of simplicity, environmental protection, low cost, and good physical properties of products.
[0004] The polymer expanded microsphere foaming method is a physical foaming method. The polymer expanded microsphere is composed of a thermoplastic polymer shell and an enclosed alkane gas. The plastic shell softens when heated and the gas inside the shell expands, thereby foaming the polymer matrix and obtaining a lightweight and porous fluororubber foam composite material. However, the addition of polymer expanded microspheres improves the insulation and heat insulation performance of FKM while greatly reducing its mechanical strength, modulus and hardness. In order to improve the performance of FKM and its products, domestic and foreign scholars have conducted a lot of modification research, including main chain modification, rubber compounding, filler filling and surface modification. Among them, filling modification has the advantages of simple process, low cost and easy promotion, and is the main way to improve the comprehensive performance of FKM products. The high-performance nanofillers commonly used in FKM modification mainly include nano-silica, carbon black, graphene, carbon nanotubes, etc. Among them, carbon nanofillers are usually expensive, single color and limited in scope of use. Nano-silica is an ideal filler for fluororubber foam composite materials because of its colorlessness, small particle size, high strength, high modulus, high hardness, high surface activity, high temperature resistance, non-toxicity and pollution-free.
[0005] Fluororubber foam composites can be used as sound insulation, buffer or sealing materials in the fields of electrical insulation, sound insulation, and semiconductor sealing. Therefore, the preparation of polymer expanded microsphere doped modified fluororubber foam composites and the research on their electrical conductivity and thermal insulation properties are extremely important for the high-quality development of the manufacturing industry. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a polymer expanded microsphere doped modified fluororubber foam composite material and its application.
[0007] The technical scheme adopted by the present invention is as follows: a polymer expanded microsphere doped modified fluororubber foam composite material, which is obtained by mixing and vulcanizing raw rubber, polymer expanded microspheres, nano-silica balls, TAIC and 2,5-dimethyl-2,5-bishexane as raw materials, wherein the mass ratio of raw rubber, polymer expanded microspheres, nano-silica balls, TAIC and 2,5-dimethyl-2,5-bishexane is 100:0-7:0-2:1-2:0.5-2.
[0008] Preferably, the preparation method comprises the following steps:
[0009] S1. Add raw rubber into a rubber mixer, then add polymer expanded microspheres, and mix evenly;
[0010] S2, adding nano-silica balls and mixing evenly;
[0011] S3, continue to add TAIC and 2,5-dimethyl-2,5-dihexane, mix evenly and let stand to obtain a composite material;
[0012] S4, vulcanizing and pressing the composite material into a shape;
[0013] S5. The pressed material is subjected to a two-stage vulcanization treatment.
[0014] Preferably, in step S1, the roller temperature is set at 30-60°C.
[0015] Preferably, in step S4, the vulcanization temperature is 130-170°C.
[0016] Preferably, in step S5, the vulcanization temperature is 180-220°C.
[0017] Preferably, the polymer expanded microspheres are composed of a thermoplastic polymer shell and liquid alkane gas sealed therein. The plastic shell softens when heated and the gas inside the shell expands, thereby foaming the polymer matrix (molded shell) and obtaining a lightweight and porous fluororubber foam composite material.
[0018] Preferably, the particle size of the nano-silica spheres is 10-30 nm.
[0019] The second aspect of the present invention provides the use of the polymer expanded microsphere doped modified fluororubber foam composite material as a buffer or sealing material in the field of electrical insulation and semiconductor sealing.
[0020] The beneficial effects of the present invention are as follows: the present invention uses polymer expanded microspheres as physical foaming agents to prepare fluororubber foam composite materials, explores the effects of the addition amount of polymer expanded microspheres, foaming temperature, etc. on the pore structure, foaming ratio, density, thermal insulation performance and mechanical properties of fluororubber foam composite materials, and screens out the optimal microsphere addition amount and foaming temperature. On this basis, by adding different contents of nano-silica microspheres, the effects on mechanical properties such as mechanical strength, modulus, hardness and wear resistance of fluororubber, as well as color properties such as haze and transmittance are investigated. The results show that the optimal foaming temperature is 150°C, the optimal addition amount of expanded microspheres is 5phr, and the foaming ratio reaches a maximum of 1.169 at this time. The optimal addition amount of nano-silica microspheres is 1g, and the addition of nano-silica can effectively enhance its tensile strength, among which the E2 sample has a maximum tensile strength of 1.9MPa and a minimum elongation at break of 127.6%; at the same time, the addition of nano-silica microspheres can effectively reduce its conductivity, which can be used in the fields of electrical insulation and semiconductor sealing manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0022] Figure 1 The present invention provides a process for preparing the fluororubber foam composite material;
[0023] Figure 2 SEM images of polymer expanded microspheres at different temperatures: (a) 130°C, (b) 140°C, (c) 150°C, (d) 160°C, (e) 170°C;
[0024] Figure 3 The infrared spectra of the fluororubber foam composite materials prepared in Examples 1-4 and Comparative Example 1;
[0025] Figure 4 (a) tensile strength and (b) elongation at break of the fluororubber foam composite materials prepared in Examples 1-4 and Comparative Example 1;
[0026] Figure 5 (a) Shore hardness, (b) density, and (c) expansion ratio of the fluororubber foam composite materials obtained in Examples 1-4 and Comparative Example 1;
[0027] Figure 6The SEM analysis of the fracture surface of the fluororubber foam composite material prepared in Examples 1-4 and Comparative Example 1 is (a) 1phr, (b) 3phr, (c) 5phr, (d) 7phr;
[0028] Figure 7 DMA analysis of the fluororubber foam composite materials prepared in Examples 1-4 and Comparative Example 1: (a) storage modulus E'; (b) loss factor tanδ;
[0029] Figure 8 Contact angle analysis of the fluororubber foam composite materials prepared in Examples 1-4 and Comparative Example 1 (ab) Contact angle test: 1-5 are 0, 1, 3, 5, 7 phr groups of water contact angle test, 1'-5' are 0, 1, 3, 5, 7 phr groups of diiodomethane contact angle test;
[0030] Fig. 9 is the thermal conductivity of the fluororubber foam composite material obtained in Examples 1-4 and Comparative Example 1;
[0031] Fig.10 The figure is a test result of the sound insulation performance of the fluororubber foam composite material prepared in Examples 1-4 and Comparative Example 1;
[0032] Fig.11 Nano-SiO 2 transmission electron microscopy;
[0033] Fig.12 (a) tensile strength and (b) elongation at break of the modified fluororubber foam composite materials obtained in Examples 3 and 5-8;
[0034] Fig.13 (a) Shore hardness and (b) density of the modified fluororubber foam composite materials obtained in Examples 3 and 5-8;
[0035] Fig.14 (a) Thermal conductivity, (b) electrical conductivity of the modified fluororubber foam composite materials obtained in Examples 3, 5-8. DETAILED DESCRIPTION
[0036] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0037] The raw materials and instruments involved in the embodiments of the present invention are shown in Tables 1 and 2 below:
[0038] Table 1 Experimental raw materials
[0039]
[0040] Table 2 Experimental instruments
[0041]
[0042]
[0043] Example 1
[0044] (1) Weighing
[0045] The raw materials were weighed according to the following mass parts (phr): 100 parts of 757 raw rubber; 1 part of polymer expanded microspheres; 1.75 parts of TAIC; and 1 part of 2,5-dimethyl-2,5-bishexane.
[0046] (2) Mixing and rubber making
[0047] Set the roller gap of the open rubber mixer to 0.2 mm and control the roller temperature at 45°C. After the machine reaches the set conditions, start the machine and gradually add the raw rubber. Then, gradually add the polymer expanded microspheres, mix them using the triangle bag method and further mix them after ensuring uniform distribution. Then add TAIC and 2,5-dimethyl-2,5-dihexane in sequence. After the addition is completed, adjust the roller gap to 1.2 mm and maintain the roller temperature at 45°C until the composite material is mixed evenly and has a moderate thickness. Finally, take out the composite sheet and mark it appropriately for subsequent identification.
[0048] (3) Let stand
[0049] After the mixing is completed, let it stand for 24 hours.
[0050] (4) One-stage vulcanization
[0051] The first stage of vulcanization is processed in a flat vulcanizer, and the composite material is pressed into a rubber sample and a rubber seal ring of 18 cm×18 cm×2 mm by vulcanization. The parameters of the vulcanization process are set as follows: pressure 10 MPa, temperature 150°C, and duration 10 minutes.
[0052] (5) Two-stage vulcanization
[0053] The rubber sample and rubber seal ring were subjected to secondary vulcanization treatment in a constant temperature blast oven. The specific secondary vulcanization parameters were: the temperature was set at 200°C and the duration was 2 hours.
[0054] Example 2
[0055] The difference between this embodiment and embodiment 1 is that in step (1), the raw materials are weighed according to the following mass parts: 100 parts of 757 raw rubber; 3 parts of polymer expanded microspheres; 1.75 parts of TAIC; and 1 part of 2,5-dimethyl-2,5-bishexane.
[0056] Example 3
[0057] The difference between this embodiment and embodiment 1 is that in step (1), the raw materials are weighed according to the following mass parts: 100 parts of 757 raw rubber; 5 parts of polymer expanded microspheres; 1.75 parts of TAIC; 1 part of 2,5-dimethyl-2,5-bishexane. The sample prepared in this embodiment is recorded as E0.
[0058] Example 4
[0059] The difference between this embodiment and embodiment 1 is that in step (1), the raw materials are weighed according to the following mass parts: 100 parts of 757 raw rubber; 7 parts of polymer expanded microspheres; 1.75 parts of TAIC; and 1 part of 2,5-dimethyl-2,5-bishexane.
[0060] Example 5
[0061] The difference between this embodiment and embodiment 1 is that in step (1), the raw materials are weighed according to the following mass parts: 100 parts of 757 raw rubber; 5 parts of polymer expanded microspheres; 0.5 parts of nano-silica microspheres; 1.75 parts of TAIC; 1 part of 2,5-dimethyl-2,5-bis-hexane;
[0062] In step (2), after the polymer expanded microspheres and the raw rubber are uniformly mixed, the nano-silica microspheres are then added and fully mixed until uniform. Then TAIC and 2,5-dimethyl-2,5-dihexane are added in sequence. After the addition is completed, the roller distance is adjusted to 1.2 mm and the roller temperature is maintained at 45°C until the composite material is uniformly mixed and has a moderate thickness. Finally, the composite material sheet is taken out and appropriately marked for subsequent identification.
[0063] The sample prepared in this example is denoted as E1.
[0064] Example 6
[0065] The difference between this embodiment and embodiment 5 is that in step (1), the raw materials are weighed according to the following mass parts: 100 parts of 757 raw rubber; 5 parts of polymer expanded microspheres; 1 part of nano-silica microspheres; 1.75 parts of TAIC; and 1 part of 2,5-dimethyl-2,5-bishexane.
[0066] The sample prepared in this example is recorded as E2.
[0067] Example 7
[0068] The difference between this embodiment and embodiment 5 is that in step (1), the raw materials are weighed according to the following mass parts: 100 parts of 757 raw rubber; 5 parts of polymer expanded microspheres; 1.5 parts of nano-silica microspheres; 1.75 parts of TAIC; and 1 part of 2,5-dimethyl-2,5-bishexane.
[0069] The sample prepared in this example is recorded as E3.
[0070] Example 8
[0071] The difference between this embodiment and embodiment 5 is that in step (1), the raw materials are weighed according to the following mass parts: 100 parts of 757 raw rubber; 5 parts of polymer expanded microspheres; 2 parts of nano-silica microspheres; 1.75 parts of TAIC; and 1 part of 2,5-dimethyl-2,5-bishexane.
[0072] The sample prepared in this example is denoted as E4.
[0073] Comparative Example 1
[0074] The difference between this comparative example and Example 1 is that in step (1), the raw materials are weighed according to the following mass parts: 100 parts of 757 raw rubber; 1.75 parts of TAIC; 1 part of 2,5-dimethyl-2,5-bishexane; and no polymer expanded microspheres are added in step (2).
[0075] 1. Study on the influence of the content of polymer expanded microspheres in Examples 1-4 and Comparative Example 1 on the foaming ratio, mechanical properties and thermal conductivity of fluororubber
[0076] 1. SEM analysis of polymer expanded microspheres at different temperatures
[0077] The microscopic morphology of the foaming agent (polymer expanded microspheres) at different temperatures was characterized by SEM, such as Figure 2 As shown. Figure 2 It can be seen that after being treated at 130℃, the microspheres began to expand; when the temperature was below 140℃, the microspheres partially expanded; when treated at 150℃, the microspheres were almost completely expanded and the microspheres were evenly distributed; when the temperature was raised to 160℃, it was found that the expansion degree of the microspheres was equivalent to that of the microspheres treated at 150℃, but its distribution was narrower and the expanded microspheres were more concentrated; when the temperature reached 170℃, the number of expanded microspheres decreased sharply. This is because the temperature was too high, causing the gas in the shell to expand due to heat and escape from the shell, and most of the microspheres squeezed each other and burst, and the outer shell was broken and adhered. It can be seen that the optimal foaming temperature of polymer expanded microspheres is 150-160℃.
[0078] 2. FTIR analysis of fluororubber foam composites
[0079] Infrared spectroscopy analysis was performed on the fluororubber foam composite materials with different microsphere addition amounts in Examples 1-4 and Comparative Example 1. The results are as follows: Figure 3 shown.
[0080] Material in 499cm -1 、885cm -1 、1132cm -1 、1396cm -1 、1694cm -1 、2963cm-1 There are absorption peaks of different intensities at 3 Group, -CF 2 -group, -CF-group, C=C bond, CH absorption peak. Among them, 1694cm -1 The non-conjugated C=C bond at 1694 cm-1 can preliminarily prove the occurrence of defluorination hydrogenation reaction and oxidation reaction during the vulcanization process. It was found that the 1694 cm-1 ions still existed before the addition of 5 phr of microspheres. -1 peak, reaching 1694cm after 5phr -1 The peak at 40° disappears, which proves that the defluorination hydrogenation reaction and oxidation reaction can only completely occur during the vulcanization process when the microsphere addition amount reaches 5 phr.
[0081] 3. Mechanical properties
[0082] In order to study the effect of the amount of polymer expanded microspheres added on the mechanical properties of foam composites, the measurement results are shown in Table 3. In order to study the effect of the amount of polymer expanded microspheres added on the tensile properties of foam composites, a universal tensile testing machine was used to measure the results as shown in Table 3. Figure 4 As shown in Table 6 and Figure 4 a, 4b show that the addition of polymer expanded microspheres significantly reduces the tensile strength and elongation at break of the composite material. As the amount of polymer expanded microspheres added increases, the tensile strength also slowly increases, and the elongation at break shows a trend of first rising and then falling. When the amount of foaming agent added reaches 5phr, the elongation at break is the highest, reaching 130.9%. This is because the polymer expanded microsphere is a rigid regular material. When it is evenly distributed in the FKM matrix to form a regular network structure, it will improve the mechanical properties of fluororubber foam composite materials under certain circumstances. However, with the increase in the amount of expandable microspheres added, the composite material has more and more pores caused by the foaming reaction, which greatly affects its mechanical properties, and the negative impact of the pores on its mechanical properties is greater than the positive effect of the expandable microspheres on its mechanical properties, resulting in a decrease in mechanical properties.
[0083] Table 3 Mechanical properties of fluororubber foam composites
[0084]
[0085] To study the effect of the amount of polymer expanded microspheres added on the hardness of foam composites, the results are as follows Figure 5As shown in a. As can be seen from the chart, adding polymer expanded microspheres will significantly reduce its hardness; with the increase in the amount of microspheres added, the hardness of the foam composite material is slowly increasing, but the increase is not large. For example, taking the sample with a microsphere content of 3phr as a reference, the hardness of the 5phr and 7phr samples only increased by 4.2% and 8.1%. The reason for the slight increase in hardness is that the polymer expanded microspheres are a rigid regular material. When they are evenly distributed inside the FKM matrix, they can form a firm network structure, which can appropriately enhance its hardness.
[0086] The density of the material is measured by weighing, such as Figure 5 As shown in Figure b, adding polymer expanded microspheres can significantly reduce its density; the density of the material before vulcanization increases first and then slightly decreases with the increase in the amount of microspheres added, and the density is the highest when 5phr expanded microspheres are added, which is 1.488g·cm -3 The density of the vulcanized material first decreases and then slightly increases with the increase of the amount of microspheres added. The density is the lowest when 5phr of expanded microspheres are added, which is 1.273g·cm -3 By calculating the expansion ratio E L =ρ 前 / ρ 后 , the results are as follows Figure 5 c. Figure 5 c and Table 6 show that with the increase of the amount of microspheres added, the foaming ratio shows a trend of first rising and then basically stabilizing, which is positively correlated with its density before vulcanization and negatively correlated with its density after vulcanization. This is because after adding a small amount of expanded microspheres in the early stage (before 5phr), with the increase of the amount of microspheres added, for FKM before vulcanization, only a small part of the expanded microspheres expand, and more of them act as fillers. Because the expanded microspheres are rigid materials and can form a network structure in the FKM matrix, the density is getting higher and higher; while for the expanded microspheres after vulcanization, they are almost completely expanded, and there are more and more pores inside the sample. The internal environment of FKM can carry these pores, and its density is naturally getting lower and lower, and the foaming ratio is getting higher and higher. After the amount of microspheres added exceeds 5phr, the number of microspheres per unit volume is too large, the expansion volume becomes smaller under the influence of mutual squeezing when heated and expanded, and the expansion efficiency becomes lower, resulting in the gradual decrease in the effect of the amount of polymer expanded microspheres on the foaming ratio of the sample. Therefore, after the amount of addition exceeds 5phr, its foaming ratio and density will basically tend to be stable.
[0087] In summary, when the amount of microspheres added is 5phr, the foaming material has an excellent foaming ratio, and compared with other gradient experiments, the comprehensive mechanical properties of the 5phr group are also more prominent. Therefore, in this experiment, the most appropriate amount of microspheres added is 5phr.
[0088] 4. Tensile fracture surface analysis of fluororubber foam composites
[0089] Figure 6 The microscopic conditions of the macroscopic tensile fracture surface of the composite material with different microsphere addition amounts are shown respectively. Figures a, b, c, and d are SEM images of the fracture surface of the material with microsphere addition amounts of 1phr, 3phr, 5phr, and 7phr, respectively. Figure 6 a and 6b show that with the increase of the amount of microspheres added, the pores per unit area increase. Figure 6 In a and 6b, the pores are squeezed and deformed against each other and are unevenly distributed; Figure 6 The pore structure formed in c is very uniform and there is no mutual extrusion and deformation between the pores; Figure 6 Although the pores in d are very dense, there are mutual squeezing and deformation between the pores, and the size is not uniform. This is because before 5phr, with the increase of microsphere addition, the foaming ratio also increases, and the pores per unit area also increase; after exceeding 5phr, the number of microspheres per unit volume is too large, and the expansion volume becomes smaller and the expansion efficiency becomes lower due to mutual squeezing when heated and expanded, resulting in the gradual decrease in the effect of the addition of polymer expanded microspheres on the foaming ratio of the sample. In summary, the optimal microsphere addition amount is 5phr.
[0090] 5. Dynamic Thermomechanical Analysis
[0091] Figure 7 The relationship between the storage modulus and loss factor tanδ of fluororubber foam composites with different microsphere addition amounts and temperature was studied by DMA. The results are as follows Figure 7 a, 7b. Figure 7 It can be seen from a that the addition of polymer expanded microspheres will reduce its storage modulus. As the amount of addition increases, its storage modulus will be lower. After the addition exceeds 5phr, its storage modulus basically does not change (the 5phr and 7phr curves almost overlap). This is attributed to the fact that the expanded microspheres are rigid and regular materials. They are distributed inside the FKM matrix and can form a network cross-linked structure with the FKM molecules. This cross-linked network structure improves the interface interaction between the microspheres and the FKM matrix. As the amount of microspheres added increases, its foaming ratio also increases, the content of microspheres used to form a network structure decreases, and the pore structure formed by the expansion of microspheres is not conducive to the enhancement of the storage modulus. Therefore, the storage modulus of low-content expanded microspheres will be greater than that of high-content expanded microspheres. After exceeding 5phr, the number of microspheres per unit volume is too large, the expansion volume becomes smaller under the influence of mutual squeezing during thermal expansion, and the expansion efficiency becomes lower, resulting in the gradual decrease in the effect of the addition of polymer expanded microspheres on the foaming ratio of the sample, and therefore the effect on the storage modulus also decreases.
[0092] from Figure 7As can be seen from b, with the increase of the amount of microspheres added, the peak height gradually decreases, and the curve remains almost unchanged after exceeding 5phr. This is mainly due to the reduction of the polymer fraction in a certain volume of vulcanized rubber. The interaction between the expanded microspheres and the rubber molecules will restrict the movement of the chain, thereby reducing the peak height. In the glassy and transitional states, the microspheres have lower hysteresis at a given energy input; in the rubbery state, the filler will enhance the hysteresis phenomenon. The reason is that in the glassy and transitional states, the polymer itself consumes a large proportion of the energy, while the small solid particles in the polymer matrix absorb almost no energy; when in the rubbery state, the network structure is decomposed, which leads to additional energy consumption, and therefore has higher hysteresis in the rubbery state.
[0093] 6. Contact angle analysis
[0094] Figure 8 (ab) is a comparison of the contact angle tests of water and diiodomethane. The water contact angles of the materials were 104.6°, 88.4°, 106.9°, 101.8°, and 97.7°, respectively. It was found that after the addition of expanded microspheres, the contact angle first decreased sharply and then exceeded 90° and tended to be flat, showing hydrophobicity. This may be because the outer shell of the polymer expanded microspheres is composed of polar thermoplastic resins, and because some microspheres are not expanded, these polar substances are doped inside the matrix, which greatly improves the adhesion of the material surface, enhances the surface energy between water, and improves the hydrophilicity; with the increase in the amount of microspheres added, the microspheres are almost completely expanded, so that the polar substances are all dissipated, showing hydrophobicity. The contact angles with diiodomethane were 72.7°, 74.6°, 69.5°, 68.0°, and 63.6°, respectively. It was found that with the increase in the amount of microspheres added, the contact angle became smaller and smaller, showing lipophilicity. This is because as the amount of polymer expanded microspheres increases, the surface roughness of the FKM foam composite increases, thereby reducing the contact angle of diiodomethane.
[0095] 7. Thermal conductivity
[0096] The effect of microsphere addition on the thermal conductivity of the composite material was tested by a thermal conductivity tester. The results are as follows: Fig. 9 As shown. Adding expanded microspheres can improve the thermal conductivity of FKM; as the amount of microspheres added increases, the thermal conductivity of the material also increases slightly, but after exceeding 3phr, the thermal conductivity remains basically stable. This is because the addition of expanded microspheres increases the number of heat conduction paths in the material, making it easier for heat to be conducted through contact between microspheres, thereby improving the overall thermal conductivity through the thermal bridge effect; as the amount of microspheres added increases, the foaming structure of the material tends to be stable with the foaming ratio, and the thermal conductivity coefficient also tends to be stable.
[0097] 8. Sound insulation performance
[0098] The effect of microsphere addition on the sound insulation performance of composite materials was tested by 4206 impedance tube. The results are as follows: Fig.10 As shown. In the low-frequency region, as the amount of microspheres added increases from 1phr to 7phr, the sound insulation of the material gradually increases. However, in the mid-frequency and high-frequency regions, although the increase in the amount of microspheres added reduces the sound insulation to a certain extent, the overall sound insulation is relatively high, all higher than 30dB (the sound insulation of ordinary sound insulation boards on the market), showing excellent sound insulation effect.
[0099] 2. Research Examples 3, 5-8 (E0-E4) doped with different contents of nano-SiO 2 Effects on the mechanical, thermal, electrical and color properties of fluororubber
[0100] 1. SiO 2 TEM analysis
[0101] The nano-silicon dioxide material was characterized by TEM electron microscope, and the results are as follows Fig.11 As shown in the figure, nano-silicon dioxide appears as flocculent or mesh flakes under an electron microscope, with an average particle size of about 15nm. The smaller particle size gives it a larger specific surface area and better mechanical performance enhancement effect; it has agglomeration phenomenon under an electron microscope and poor dispersibility. This is because the surface of nano-silicon dioxide has a large number of hydroxyl groups, resulting in a higher surface energy, which causes them to adsorb each other through hydrogen bonds or van der Waals forces to form aggregates; its small size effect also causes it to agglomerate.
[0102] 2. Mechanical properties
[0103] In order to study the effect of nano-silica addition on the tensile properties of fluororubber foam composites, the measured results are as follows Fig.12 As shown in the figure, it can be seen that using nano-silicon dioxide as filler can greatly improve the tensile strength of the composite material and slightly reduce the elongation at break. The E2 sample has a maximum tensile strength of 1.925MPa and a minimum elongation at break of 127.6%. This is because nano-silicon dioxide has a nano-enhancement effect in the FKM matrix, and the three-dimensional network structure formed can hinder the movement of rubber molecular chains, thereby improving the tensile strength of the composite material and reducing its elongation at break; the agglomeration effect of nano-silicon dioxide causes stress concentration and weakens the reinforcement effect on the material.
[0104] In order to investigate the effect of nano-silicon dioxide addition on the hardness and density of fluororubber foam materials, the results are as follows: Fig.13 As shown in the figure, as the amount of nano-silicon dioxide added increases, the hardness gradually increases. Compared with E0, E2-E4 increased by 4%, 4.9% and 7.7% respectively. The reason is that when the size of nano-silicon dioxide particles is reduced to the nanometer level, it has a nano-enhancement effect. Fig.13As shown in Figure 2, the density of fluororubber before vulcanization generally increases with the increase of nano-silica content. After vulcanization, the density increases more obviously than that of the blank sample E0, with the maximum density of 1.318 g·cm at E2. -3 .
[0105] Table 4 Mechanical properties of modified fluororubber foam composites
[0106]
[0107] 3. Thermal and electrical conductivity
[0108] In order to study the effect of nano-silica addition on the thermal conductivity and electrical conductivity of fluororubber foam composite materials, thermal conductivity tester and digital multimeter were used to measure the thermal conductivity and electrical conductivity. The results are shown in Fig.14 As shown. The addition of nano-silica has little effect on its thermal conductivity. The maximum value of E2 thermal conductivity is 0.1668W / m·K, which is 4.4% higher than the blank sample E0 thermal conductivity of 0.1597W / m·K. As the amount of nano-silica added increases, the conductivity of the composite material gradually decreases; compared with the initial material, the conductivity is 1.16×10 -11 S / m, E1, E2, E3, and E4 decreased by 50.69%, 59.5%, 64.8%, and 68.7% respectively. This is because the agglomeration of nano-silicon dioxide is not conducive to the formation of a conductive network in the matrix and its resistivity is extremely high. In summary, the addition of nano-silicon dioxide can effectively reduce the electrical conductivity of fluororubber foam materials and has a certain effect on improving thermal conductivity.
[0109] 4. Color performance
[0110] In order to investigate the effect of different contents of nano-silica on the color performance of fluororubber foam composite materials, this experiment tested its haze and transmittance with a haze meter, and the results are shown in Table 5. It can be seen that the haze values of the five black samples are all 100.00; the transmittance is low, and the transmittance of the E2 sample is the highest. This may be caused by the high crosslinking density.
[0111] Table 5 Color properties of modified fluororubber foam composite materials
[0112] E0 E1 E2 E3 E4 Haze(H) 100.00 100.00 100.00 100.00 100.00 Transmittance(T) 0.04 0.07 0.14 0.03 0.03
[0113] In summary, the present invention explores the optimal foaming temperature of polymer expanded microspheres, and on this basis, investigates the effects of polymer expanded microspheres and nano-silicon dioxide content on the mechanical, thermal insulation, electrical, and color properties of fluororubber foam composites, and draws the following conclusions:
[0114] (1) The microstructure of microspheres expanded at different temperatures was characterized by SEM, and it was found that the optimal foaming temperature was around 150°C;
[0115] (2) Through infrared spectroscopy analysis of fluororubber foam composites with different microsphere addition amounts, it was found that the peak at 1694 cm -1 The characteristic peak disappears, proving that the defluorination hydrogenation reaction and oxidation reaction completely occur during the vulcanization process when the microsphere addition amount reaches 5phr;
[0116] (3) Through the mechanical, thermal properties and dynamic thermomechanical analysis of fluororubber foam composites with different microsphere addition amounts, it was found that after adding 5phr of microspheres, the material had excellent foaming ratio, tensile strength and hardness;
[0117] (4) By characterizing the mechanical properties of fluororubber foam composites with different amounts of nano-silica microspheres, it was found that the addition of nano-silica can effectively enhance its tensile strength and reduce its elongation at break, and the hardness is improved to a certain extent;
[0118] (5) By characterizing the thermal and electrical properties of fluororubber foam composites with different amounts of nano-silica microspheres added, it was found that the addition of nano-silica microspheres can effectively reduce its electrical conductivity, but has little effect on thermal conductivity, but the improvement of thermal conductivity is not obvious.
[0119] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A polymer expanded microsphere doped modified fluororubber foam composite material, characterized in that: The invention is prepared by mixing raw rubber, polymer expanded microspheres, nano silica spheres, TAIC and 2,5-dimethyl-2,5-bishexane as raw materials and then vulcanizing them, wherein the mass ratio of raw rubber, polymer expanded microspheres, nano silica spheres, TAIC and 2,5-dimethyl-2,5-bishexane is 100:0-7:0-2:1-2:0.5-2.
2. The polymer expanded microsphere doped modified fluororubber foam composite material according to claim 1, characterized in that: The preparation method comprises the following steps: S1. Add raw rubber into a rubber mixer, then add polymer expanded microspheres, and mix evenly; S2, adding nano-silica balls and mixing evenly; S3, continue to add TAIC and 2,5-dimethyl-2,5-dihexane, mix evenly and let stand to obtain a composite material; S4, vulcanizing and pressing the composite material into a shape; S5. The pressed material is subjected to a two-stage vulcanization treatment.
3. The polymer expanded microsphere doped modified fluororubber foam composite material according to claim 2, characterized in that: In step S1, the roller temperature is set at 30-60°C.
4. The polymer expanded microsphere doped modified fluororubber foam composite material according to claim 2, characterized in that: In step S4, the vulcanization temperature is 130-170°C.
5. The polymer expanded microsphere doped modified fluororubber foam composite material according to claim 1, characterized in that: In step S5, the vulcanization temperature is 180-220°C.
6. The polymer expanded microsphere doped modified fluororubber foam composite material according to claim 1, characterized in that: The polymer expanded microspheres are composed of a thermoplastic polymer shell and liquid alkane gas sealed therein.
7. The polymer expanded microsphere doped modified fluororubber foam composite material according to claim 6, characterized in that: The shell of the foamed microspheres is a thermoplastic methacrylate polymer and the core is liquid isopentane.
8. The polymer expanded microsphere doped modified fluororubber foam composite material according to claim 1, characterized in that: The particle size of the nano silicon dioxide sphere is 10-30nm.
9. Use of the polymer expanded microsphere doped modified fluororubber foam composite material as claimed in any one of claims 1 to 8 as a buffer or sealing material in the field of electrical insulation and semiconductor sealing.
Citation Information
Cited By
Preparation method of high-strength high-foaming fluororubber foam material
CN122483392A